PERTANGGUNGJAWABAN PIDANA PELAKU PENGHINAAN MELALUI LAYANAN PESAN SINGKAT ATAU SMS (SHORT MESSAGE SERVICE) (Studi Putusan: Pengadilan Negeri Sumenep Nomor: 70/Pid.B/2010/PN.SMP, Putusan Pengadilan Negeri Pati Nomor: 45/Pid.Sus/2013/PN.Pt, Putusan Pengadil - Rumia R.A.C Lumbanraja; Syafruddin Kalo; Madiasa Ablisar; Keizerina Devi (USU LAW JOURNAL, 2017)
ABSTRACT Technological Development causes new legal problem, humiliation which is done through electronic Short Message Service (SMS). Humiliation case is regulated in Article 310-321 of the KUHP (the Criminal Code). Since SMS is an electronic service, the Government issued UU ITE 9Law No. 11/2008 on ITE or Electronic Information and Technology). There is the difference in the implementation of law: 1) how about the implementation of the evidence for humiliation criminal acts through SMS, and 2) how about the criminal liability of perpetrator of humiliation through SMS.  From the evidence aspect, the KUHP has no evidence for electronic case while SMS is interpreted as a written form which is regarded and categorized in the KUHAP as a letter as it is stipulated in Article 187, letter d of the KUHAP which is only in effect if there is another evidence related to other evidence. According to Article 1, figure 1 of Law No. 11/2008 on ITE, SMS is electronic information, electronic data in a written form which can be accepted as valid evidence as it is stipulated in Article 5 of UU ITE. The perpetrator of humiliation through SMS has legal liability since it has fulfilled the counts to criminal act and its consequences, the existence of guilt that the perpetrator intentionally sends SMS containing humiliation by attacking one’s dignity and good reputation in the SMS, and the counts to eliminate criminal act since there is no apology by the perpetrator as it is stipulated in the KUHP so that criminal sanction can be imposed on the perpetrator.   Keywords: Criminal Liability, Humiliation, Short Message Service or SMS